Effect of gamma radiation on fungal growth stages and mechanical properties of traditional Japanese paper - Nguyễn, Thị Thùy Linh (Elsevier B.V., 2021)
In this study, we investigated the effect of gamma irradiation on fungal growth and mechanical properties of the traditional Japanese paper, Kohzo-gami, infected by mesophilic fungi such as Aspergillus sydowii, Penicillium chrysogenum, and Cladosporium cladosporioides. The radiation sensitivities of dormant conidium-, germinating conidium-, and mycelium-contaminated wet and dry paper were also determined. A radiation dose capable of inactivating 50% of a 30-sample population was used for comparison. Our results showed that the 50% inactivation dose did not significantly differ between wet and dry dormant conidia. However, the survival percentage of dry dormant conidia was higher than that of wet dormant conidia at a high radiation dose. In contrast, the 50% inactivation doses for dry germinating conidia and dry mycelia were significantly lower than those for wet germinating conidia and wet mycelia, respectively. These results indicate that drought stress increased the radiation sensitivity of germinating conidia and mycelia. We also investigated the mechanical properties of Kohzo-gami irradiated at different doses. The order of the tensile strength of Kohzo-gami relative to that of control samples was as follows: 10 kGy > 30 kGy > 40 kGy. This result suggests that even a 10 kGy radiation dose can affect the mechanical properties of paper. The color change level of Kohzo-gami increased significantly at all doses; however, the National Bureau of Standards rating showed only “slight change” at all doses. The radiation doses required for fungal disinfection varied considerably depending on the fungal species and the total number of fungal cells on contaminated paper. Therefore, it was difficult to determine the standard exposure dose for treatment. However, paper sterilization might not be required, as a combination of low-dose radiation and dryness can effectively kill fungal mycelia on contaminated paper.